(untitled) (Medico Legal Update, 2020)
Background: inhibin B considered a sensitive marker for follicles numbers of the ovary. Inhibin B levels increased with overnighted, lipedema and PCOS women. PCOS affects women in menstrual age. Obesity and insulin resistance have an association with PCOS. This syndrome increases LH, FSH, Prolactin. and testosterone hormonal levels. Aim: examine the role of inhibin B in polycystic ovary syndrome (PCOS) with type 2DM patients, and to investigate the correlation between these quantities with serum inhibin B for women on the 12th day of their ovulation developments and correlation of inhibin with other biochemical parameters in those patients. Patient and Method: sixty women included in this study divided into two groups of 30 subjects. The first group is for women who had PCOS with type 2DM, and the second for control subjects. PCOS with type 2DM patients diagnosed according to Rotterdam ESHRE/ASRAM. The biomedical test is done for FBS, Cholesterol, TG, LDL, HDL, HbA1c for all subjects included in this study. Results: BMI, weight, prolactin and testosterone, FBS, cholesterol, TG, LDL, HDL, HbA1c had significantly higher levels in PCOS women with type 2DM. while inhibin B level showed to be significantly lower in PCOS with type 2DM. when this study attempted to find the correlation between the inhibin B with the biochemical tests, only the TG and HbA1c show a significant correlation in PCOS with type 2DM women. Discussion: The high levels of biochemical parameters for diabetic female patients’ groups with PCOS are due to the association of PCOS with insulin resistance and obesity. So, the low inhibin B levels in PCOS with type 2DM and its correlation with HbA1c and TG in the PCOS group could be an indication for using inhibin B as a type 2 DM marker. This study supported by Katrine et al 2017 when found out that when they diagnosed type 2DM at a younger age the levels of event rate (HbA1c and FBS) was higher in PCOS compared with controls Conclusion: There is a significant correlation in inhibin-B levels with HbA1c and TG levels in PCOS women with type 2 DM.